Localization of Interictal Epileptiform Activity Using Magnetoencephalography with Synthetic Aperture Magnetometry in Patients with a Vagus Nerve Stimulator - Stapleton-Kotloski, Jennifer R.; Kotloski, Robert J.; Boggs, Jane A.; Popli, Gautam; O’Donovan, Cormac A.; Couture, Daniel E.; Cornell, Cassandra; Godwin, Dwayne W. (Frontiers in Neurology, 2014)
Magnetoencephalography (MEG) provides useful and non-redundant information in the evaluation of patients with epilepsy, and in particular during the pre-surgical evaluation of pharmaco-resistant epilepsy. Vagus nerve stimulation (VNS) is a common treatment for pharmaco-resistant epilepsy. However interpretation of MEG recordings from patients with a VNS is challenging due to the severe magnetic artifacts produced by the VNS. We used synthetic aperture magnetometry (g2) (SAM(g2), an adaptive beamformer that maps the excessive kurtosis, to map interictal spikes to the coregistered MRI image, despite the presence of contaminating VNS artifact. We present a series of eight patients with a VNS who underwent MEG recording. Localization of interictal epileptiform activity by SAM(g2) is compared to invasive electrophysiologic monitoring and other localizing approaches. While the raw MEG recordings were uninterpretable, analysis of the recordings with SAM(g2) identified foci of peak kurtosis and source signal activity that was unaffected by the VNS artifact. SAM(g2) analysis of MEG recordings in patients with a VNS produces interpretable results and expands the use of MEG for the pre-surgical evaluation of epilepsy.